Optical properties of mice's stool in 550 to 1000 nm wavelength range. Issue 2 (11th October 2017) - Isler, Helene; Germanier, Catherine; Ahnen, Linda; Jiang, Jingjing; Lindner, Scott; Di Costanzo Mata, Aldo; Karen, Tanja; Sánchez Majos, Salvador; Wolf, Martin; Kalyanov, Alexander
Abstract : The aim of this work was to measure optical properties of stool of mice to provide this relevant wavelength‐dependent behavior for optical imaging modalities such as fluorescent molecular tomography and near‐infrared optical tomography. BALB/c nude female mice were studied and optical properties of the stool were determined by employing the inverse adding‐doubling approach. The animals were kept on chlorophyll‐free diet. Nine stool samples were measured. The wavelength‐dependent behavior of absorption and scattering in 550 to 1000 nm range is presented. The reduced scattering spectrum is fitted to the Mie scattering approximation in the near‐infrared (NIR) wavelength range and to the Mie + Rayleigh approximation in visible/NIR range with the fitting coefficients presented. The study revealed that the absorption spectrum of stool can lead to crosstalk with the spectrum of hemoglobin in the NIR range. Abstract : Stool optical properties of the laboratory mouse, that is, absorption, reduced scattering and anisotropy factor, are determined. These parameters are required for accurate modeling of diffuse light propagation through the mouse body in diffuse optical imaging modalities. Due to small size of the volume and high depth of light penetration, the light reaches internal organs, including the large intestine, where the stool optical properties are representative.